Study on the health impacts of childhood asthma in China caused by air pollution - Fangfang Ruan; Kangwei Li; Kena Mi (PLoS ONE, 2025)
Asthma is one of the major disease burdens in children. Ambient air pollution is associated with the prevalence and exacerbation of childhood asthma. Over recent decades, China has exhibited a persistent upward trajectory in pediatric asthma prevalence. This epidemiological trend necessitates a comprehensive evaluation of the health impacts associated with childhood asthma attributable to ambient air pollution exposure. This study selected PM 2.5 , NO 2 , and O 3 as representative ambient air pollutants in China, and obtained exposure-response parameters required for health impact assessment through Meta-analysis. Then the study evaluated the health impacts of childhood asthma aged 0–14 years attributable to air pollution in 336 cities across China based on national real-time air quality monitoring data. Hypothetical scenarios were also constructed to predict the preventable childhood asthma disease burden under different air pollution control levels. The results showed that in 2019, air pollution caused 264,800–467,100 childhood asthma exacerbation cases and 622,800–1115,000 incident asthma cases among children, accounting for 7.1% − 12.5% and 31.4% − 56.2% of the total asthma children visits and incidence of childhood asthma in that year. The pollutant that has the greatest impact on childhood asthma is O 3 , followed by PM 2.5 and NO 2 . The health impacts of the three pollutants were spatially distributed to be higher in the central and southern regions of China, and lower in the southwestern, northeastern, and northwestern regions. Chongqing was the city most affected by three types of pollutants. When pollutant concentrations comply with the WHO guidelines, up to 267,900 cases of childhood asthma exacerbations and 873,900 new-onset childhood asthma cases could be averted.